2017
DOI: 10.3390/en10020187
|View full text |Cite
|
Sign up to set email alerts
|

Using a Reactive Transport Simulator to Simulate CH4 Production from Bear Island Basin in the Barents Sea Utilizing the Depressurization Method†

Abstract: Abstract:The enormous amount of methane stored in natural gas hydrates (NGHs) worldwide offers a significant potential source of energy. NGHs will be generally unable to reach thermodynamic equilibrium at their in situ reservoir conditions due to the number of active phases involved. Lack of reliable field data makes it difficult to predict the production potential and safety of CH 4 production from NGHs. While the computer simulations will never be able to replace field data, one can apply state-of-the-art mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…As shown in Table 6, (2,8) , which meant intrinsic permeability k and initial NGH saturation S H0 had a more significant influence on CH 4 cumulative volume. Furthermore, when F 0.01 (2,8) > F N > F 0.05 (2,8) , crack quantity N had a significant influence on CH 4 cumulative volume, which was smaller than that of k and S H0 , and the significance of interaction between k, S H0 , and N were small. The results showed that the impact of intrinsic permeability, initial NGH saturation, and the stimulation effect on NGH conversion efficiency were significant; however, the interaction had no significant effect.…”
Section: Analysis Of the Factors' Significance And Influence Rules Onmentioning
confidence: 98%
See 2 more Smart Citations
“…As shown in Table 6, (2,8) , which meant intrinsic permeability k and initial NGH saturation S H0 had a more significant influence on CH 4 cumulative volume. Furthermore, when F 0.01 (2,8) > F N > F 0.05 (2,8) , crack quantity N had a significant influence on CH 4 cumulative volume, which was smaller than that of k and S H0 , and the significance of interaction between k, S H0 , and N were small. The results showed that the impact of intrinsic permeability, initial NGH saturation, and the stimulation effect on NGH conversion efficiency were significant; however, the interaction had no significant effect.…”
Section: Analysis Of the Factors' Significance And Influence Rules Onmentioning
confidence: 98%
“…By comparing F i and F 0.05 (2,8) and F 0.01 (2,8) , the impact of factor i was significant when F i > F 0.05 (2,8) , and had a more significant influence when F i > F 0.01 (2,8) . As shown in Table 6, (2,8) , which meant intrinsic permeability k and initial NGH saturation S H0 had a more significant influence on CH 4 cumulative volume.…”
Section: Analysis Of the Factors' Significance And Influence Rules Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, methane hydrate is the most widely-distributed in nature [1][2][3][4][5]. Marine gas hydrate is mainly developed in hydrate stability zones (HSZ) below a 500-m water depth in the open ocean, where temperatures and pressures are suitable for its spontaneous formation.…”
Section: Introductionmentioning
confidence: 99%
“…Fracturing technology can be divided into vertical and horizontal fracturing (Figure 2), according to the different characteristics of the formations [35]. Increasing the permeability of the hydrate layer can improve heat and mass transfer efficiency, increase the gas migration channels in the hydrate layer, accelerate the hydrate dissociation and discharge, and increase the gas production rate and the cumulative production of CH4 [4,13,28,30,36].…”
Section: Introductionmentioning
confidence: 99%